61 Donors Per Million: A Successful, State-Wide Donation Performance Improvement Initiative. (August 2017) - Schimpf, Christopher; O'Shaughnessy, Gweneth; Hasz, Richard; Nathan, Howard
Abstract : Background: Practice and results vary widely between hospitals, and often between institutions in the same healthcare system. This state contains eight hospitals representing six healthcare systems, including two transplant centers and two level 1 trauma centers, serving a population of approximately 952, 000. Prior to the Initiative, there was not one centralized forum for facilitating sharing of best practices or collateral learning. Identification and adherence to a single set of best demonstrated practices across multiple health systems can raise donation rates. Aim: To launch and leverage a statewide performance improvement initiative to increase organ and tissue donation across every hospital by reducing variability and standardizing practice within and among each of the hospital systems. Methods: Historic hospital development strategy encompassed proactive, comprehensive education, routine case follow up, relationship building practices, and multidisciplinary Donation Councils, as well as other methods, at each hospital in the state. Ten years of data showed an average conversion rate of 57%. To optimize the process and outcomes, the OPO partnered with various state professional organizations, each health system, and the state department of health to "Create and Sustain a Culture Where Optimal Donation Practices and Collaboration Are Embraced, Resulting in a Sustained Organ Donation Rate of At Least 65%". The OPO and hospitals together implemented a concentrated, multi-faceted approach, championed by a core group of approximately 50 multidisciplinary clinicians and administrators representing 8 hospitals. Improvements focused on timely referral, planned and collaborative family conversations about donation, hard-wired case reviews and mutual critique, and a bolstered education schedule for members of the health care teams. The core group convened quarterly to exchange information and compare experience and results, ensure standardization, and engage in collaborative learning. Between each quarterly meeting, members of the core group were responsible for instituting new practices and ensuring adherence to best practice at their home institutions. Results: Unprecedented statewide increases in donation were observed: achievement of a 62% conversion rate during the initiative compared to 57% over the previous ten years. Conclusion: A strategic, multi-faceted, and collaborative performance improvement initiative, supported by the state legislature, state nurses association, state medical society and academy of medicine, and owned by each hospital and health system, achieved never-before-seen results. Early, continuous, and active recruitment and engagement of hospital and professional organization partners by the OPO is what made these outcomes possible. Figure. No caption available.